Overall Thermal Transfer Analysis of Glazing Facade Design for Passive Building Energy Efficiency - Vighio, Anees Ahmed; Zakaria, Rozana; Ahmad, Faridahanim; Munikanan, Vikneswaran; Wahi, Noraziah; Aminuddin, Eeydzah; Wen, Thong Jia; Saha, Kamaliah Mohd; Umran, Nur Izyan Liyana; Pawłowicz, Joanna A. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The global warming incremental impacts such as temperature, precipitation, rise in sea level, and extreme weather events are indeed being observed globally. In recent decades, energy demand and greenhouse gas emissions have increased due to buildings being designed with active cooling and heating solutions, despite global attempts to reduce energy consumption. About 50 percent of all energy use is attributed to buildings.
Keywords: glazing facade; passive design; overall thermal transfer value; energy efficiency; building